Specification and Management of Methods - A Case for Multi-level Modelling - Frank, Ulrich (In: Reinhartz-Berger I., Zdravkovic J., Gulden J., Schmidt R. (eds) Enterprise, Business-Process and Information Systems Modeling. BPMDS 2019, EMMSAD 2019. Lecture Notes in Business Information Processing, vol 352. Springer, Cham, 2019)
The digital transformation creates an increasing demand for projects to prepare and realize change. The professional management of projects demands for methods. In particular, there is not alone need for method engineering, but also for managing the use of methods and for method maintenance. In this paper, it will be shown that traditional approaches to method engineering are not only limited with respect to reuse, they also do not support the integration of method engineering and method management. The approach presented in this paper addresses these limitations. It is based on a mult-level language architecture, which enables the common representation of models and code.
Keywords: Multi-level modelling; language engineering; method engineering